Maskulinitas dan bunga dalam karya R.M. Noto Soeroto Melatiknoppen: gedichten in proza dan De geur van moeders haarwrong - Suprihatin, Christina T. (Wacana, Journal of the Humanities of Indonesia, 2008)
R.M. Noto Soeroto was one of the Indonesian writers who wrote in Dutch. His poems and essays in Dutch were well appreciated by both the Dutch and the Indonesian society in the Netherlands. He published his works in Oedaya: Majalah bergambar untuk Indonesia, a magazine (1923-1931) that was founded by him. His works can be categorized as Dutch-East Indies literature. Most of his works in Dutch were written when he lived in the Netherlands and describe the Javanese culture. This article is an analysis on three of Soeroto's poems. These three poems present flowers as theme, two poems are from his anthology Melatiknoppen: gedichten in proza (1915) and one poem from De geur van moeders haarwrong (1922). Flowers are most usually seen as a symbol for women, and thus represent the idea of femininity. However, the flowers in these three poems refer to the idea of masculinity. Jasmine is no longer a symbol limited to the feminine gender. In Javanese culture, the jasmine flower attached to the hair is a symbol of femininity. The flower wrapped around the kris is a symbol of masculinity. Furthermore jasmine is a symbol for struggle. This article tries to demonstrate the presence of masculinity through the use of flowers and their role as an image of masculinity in Noto Soeroto's poems.